Dexmedetomidine’s Effects on the Livers and Kidneys of Rats with Pancreatic Ischemia-Reperfusion Injury - Bostancı H; Erel S; Küçük A; Kip G; Sezen ŞC; Gokgoz S; Atlı M; Aktepe F; Dikmen K; Arslan M; Kavutçu M (Dove Medical Press, 2024)
Hasan Bostancı,1 Selin Erel,2 Ayşegül Küçük,3 Gülay Kip,2 Şaban Cem Sezen,4 Seda Gokgoz,5 Muharrem Atlı,4 Feyza Aktepe,2 Kursat Dikmen,1 Mustafa Arslan,2,6,7 Mustafa Kavutçu5 1Gazi University Faculty of Medicine, Department of General Surgery, Ankara, Turkey; 2Gazi University Faculty of Medicine Department of Anesthesiology and Reanimation, Ankara, Turkey; 3Kutahya Health Sciences University Faculty of Medicine, Department of Physiology, Kutahya, Turkey; 4Kırıkkale University Faculty of Medicine, Department of Histology and Embryology, Kırıkkale, Turkey; 5Gazi University Faculty of Medicine, Department of Medical Biochemistry, Ankara, Turkey; 6Gazi University, Life Sciences Application and Research Center, Ankara, Turkey; 7Gazi University, Laboratory Animal Breeding and Experimental Research Center (GUDAM), Ankara, TurkeyCorrespondence: Ayşegül Küçük, Kutahya Health Sciences University, Medical Faculty, Department of Physiology, Kutahya, Turkey, Tel +90 532 675 77 05, Email aysegul.kucuk@gmail.comObjective: Pancreatic surgeries inherently cause ischemia-reperfusion (IR) injury, affecting not only the pancreas but also distant organs. This study was conducted to explore the potential use of dexmedetomidine, a sedative with antiapoptotic, anti-inflammatory, and antioxidant properties, in mitigating the impacts of pancreatic IR on kidney and liver tissues.Methods: A total of 24 rats were randomly divided into four groups: control (C), dexmedetomidine (D), ischemia reperfusion (IR), and dexmedetomidine ischemia reperfusion (D-IR). Pancreatic ischemia was induced in the IR and D-IR groups. Dexmedetomidine was administered intraperitoneally to the D and D-IR groups. Liver and kidney tissue samples were subjected to microscopic examinations after hematoxylin and eosin staining. The levels of thiobarbituric acid reactive substances (TBARS), aryllesterase (AES), catalase (CAT), and glutathione S-transferase (GST) enzyme activity were assessed in liver and kidney tissues. The serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood urea nitrogen (BUN), and creatinine were measured.Results: A comparison of the groups revealed that the IR group exhibited significantly elevated TBARS (p